Cooperative enhancer activation by TLX1 and STAT5 drives development of NUP214-ABL1/TLX1-positive T cell acute lymphoblastic leukemia - Bempt, Marlies vanden; Demeyer, Sofie; Broux, Michaël; De Bie, Jolien; Bornschein, Simon; Mentens, Nicole; Vandepoel, Roel; Geerdens, Ellen; Radaelli, Enrico; Bornhauser, Beat C.; Kulozik, Andreas; Meijerink, Jules P.; et al. (Cancer cell, 2018)
The NUP214-ABL1 fusion is a constitutively activated tyrosine kinase that is significantly associated with overexpression of the TLX1 and TLX3 transcription factors in T cell acute lymphoblastic leukemia (T-ALL). Here we show that NUP214-ABL1 cooperates with TLX1 in driving T-ALL development using a transgenic mouse model and human T-ALL cells. Using integrated ChIP-sequencing, ATAC-sequencing, and RNA-sequencing data, we demonstrate that TLX1 and STAT5, the downstream effector of NUP214-ABL1, co-bind poised enhancer regions, and cooperatively activate the expression of key proto-oncogenes such as MYC and BCL2. Inhibition of STAT5, downregulation of TLX1 or MYC, or interference with enhancer function through BET-inhibitor treatment leads to reduction of target gene expression and induction of leukemia cell death.